2016
DOI: 10.1177/0310057x1604400512
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Leak Test Technique for Endotracheal Cuff Maintenance

Abstract: Endotracheal tube (ETT) cuff pressure management is an essential part of airway management in intubated and mechanically ventilated patients. Both under-and over-inflation of the ETT cuff can lead to patient complications, with an ideal pressure range of 20-30 cmH 2 O defined. A range of techniques are employed to ensure adequate ETT cuff inflation, with little comparative data. We performed an observational cross-sectional study in a tertiary metropolitan ICU, assessing the relationship between the minimal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
16
1
2
Order By: Relevance
“…They showed that MLT causes both over- and under-inflation of the ETT cuff, and other techniques like cuff manometry should be employed. 19 Carhart et al in their study purposed to define the optimal cuff inflation volume to achieve the 20-30 cmH2o cuff pressure. They showed that the cuff inflation volume range of 6-7 mL resulted in the highest likelihood of achieving the desired cuff pressure range, while cuffs inflated with 8-10 mL resulted in dangerously high cuff pressures in all instances.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that MLT causes both over- and under-inflation of the ETT cuff, and other techniques like cuff manometry should be employed. 19 Carhart et al in their study purposed to define the optimal cuff inflation volume to achieve the 20-30 cmH2o cuff pressure. They showed that the cuff inflation volume range of 6-7 mL resulted in the highest likelihood of achieving the desired cuff pressure range, while cuffs inflated with 8-10 mL resulted in dangerously high cuff pressures in all instances.…”
Section: Introductionmentioning
confidence: 99%
“…Underinflation rates in our study (45%) were similar to those reported by Valencia et al [19] (45.3%; n = 33) after evaluating CP in adult ventilated subjects in semi-recumbent position in the adult ICU. Harvie et al [12] (24% underinflation rate) also measured using the MLT in mechanically ventilated adults in in the supine position at 30-degree head up. Other literature suggested that normal to low CP may be better than excessively high CP as injury is less likely to occur when CP was maintained at ≤20 cm H 2 O while maintaining adequate ventilation [12,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the minimal leak technique (MLT) is similar to the MOV, yet a volume of air is slowly withdrawn from the inflated cuff, while auscultating over the trachea until a leak is heard and this is recorded as the MLT. At which time air is then added to stop the cuff leak [12]. The MLT and MOV are methods routinely used in ICUs, but often result in higher CP when compared with those obtained by cuff pressure manometer [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARTICLE performed in isolation have been shown, in both adult and paediatric studies, to result in a CP outside the recommended range. [12][13][14] A survey on the minimal occlusion volume technique showed variation in technique, which may reduce efficacy. [15] If pressures above 30 cmH 2 O are required to achieve an adequate seal, the tracheal tube is likely to be too small and replacement is recommended.…”
mentioning
confidence: 99%